The place among the poets of chaste spin until the end of the Umayyad period. - Badawi Hamad AL-Zuhir, Jameel; Aayed Muhammed AL- Kaabi, Alaa (Journal of College of Education, 2020)
Place is considered one of the main and basic elements in the formation of the story, and its role is condensed in the text, and it complements the element of time, as well as its connection with the remaining narrative elements. Because it is the base on which the other elements are based؛ It is the space in which events occur, the characters move on it, and have a dialogue with one another at a certain time, and it adds the place to the aesthetic text and embodies realism in it.